CAUSAL FACTORS AFFECTING TOPURCHASE BEHAVIORON CP FRESH MART APPLICATION OFCONSUMERS INBANGKOK AND ITS VICINITY - Dunkkong, Ploypailin; Lekcharoen, Somchai (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objectives of this article were to 1) develop and validate the consistency of a casual relationship model of per chase behavior on the CP fresh mart application of consumers in Bangkok and its vicinity 2) and to study casual factors affecting purchase behavior on the CP fresh mart application of consumers in Bangkok and its vicinity. The tools used in the research were online questionnaires. The sample group consisted of454 people who have purchase on CP fresh mart application of consumers in Bangkok and its vicinity. The statistics used in data analysis were frequency, percentage and the structural equation model. The results of this research were; 1.the development of causal relationship models consisting of 4 components are 1) subjective norm 2) perceived usefulness 3)purchase intention and4) purchase behavior and the model is consistent whit the empirical data to a great extent. The statistics show the Chi-square statistics goodness fit test (χ2) = 312.28, degrees of freedom (df) = 157, CMIN/df = 1.99, GFI = 0.94, AGFI = 0.92, SRMR = 0.05, RMSEA = 0.05.The final is predictive coefficient of 0.68, indicating that the variables in the model can explain the variance of the purchase behavior on CP fresh mart application of consumers by 68 percent. 2.causal factors it was found that the purchase intention, perceived usefulness and subjective norm were respectively influenced by the purchase behavior. The results of this research are useful for entrepreneurs. CP Company on CP fresh mart application businesses are utilized to marketing plan and create marketing strategies that are suitable for consumer behavior. The results in the purchase of CP fresh mart application of consumers the future.